Emulation and experimental analysis of an axial superconductor magnetic bearing. (September 2019) - Rodriguez, E; Dos-Santos, G; Huang, Z; Wang, W; Deng, Z
Abstract: Today the high-speed and high-performance systems are each more important for many areas like industry and transport system. The magnetic levitation system can be used to improve the performance. For superconducting levitation, it is important to know the behavior of levitation force. However, its behavior is not completely known and studies about it are necessary. This work presented a description of the test bench and a brief introduction to the new software developed to the magnetic levitation measurement system (SCML-02). The system tested is compound by a superconducting bulk and permanent magnet. This system makes data acquisitions using the load cells and the data processing is built by the new software developed in the LabVIEW. The results are verified and compared by simulations which were done in the software of finite elements and measurement data of the magnetic levitation done at Federal University of Rio de Janeiro - UFRJ. The measurements of the new system show compatible results with the simulations and the measurement data done at UFRJ. Therefore, with this new software, the users can easily to do magnetic levitation measurements through an interface easy to understand.